Reversible Delithiation of Disordered Rock Salt LiVO2. Issue 11 (19th April 2018) - Baur, Christian; Chable, Johann; Klein, Franziska; Chakravadhanula, Venkata Sai Kiran; Fichtner, Maximilian
Abstract: A rigid crystal lattice, in which cations occupy specific positions, is generally regarded as a critical requirement to enable Li + diffusion in the bulk of conventional cathode materials, whereas disorder is generally considered as detrimental. Herein, we demonstrate that facile and reversible insertion and extraction of Li + is possible with LiVO2, a new cation‐disordered rock salt compound (space group: Fm 3 ‾ m ), which is, to the best of our knowledge, described for the first time. This new polymorph of LiVO2 is synthesized by mechanical alloying. Rietveld refinements of the X‐ray diffractions patterns and SAED (selected‐area electron diffraction) patterns attested the formation of the disordered LiVO2 rock salt phase. Galvanostatic cycling experiments were employed to characterize the electrochemical performance of the material, demonstrating that reversible cycling over 100 cycles with a discharge capacity around 100 mAh g −1 is possible. Abstract : With force to rock salt : A simple high‐energy ball milling approach for synthesizing a new LiVO2 polymorph with a disordered rock salt structure (space group Fm 3 ‾ m ) is presented. This compound is investigated as a cathode material in lithium‐ion batteries. Despite the disorder, LiVO2 exhibits a stable electrochemical performance.